Curial deference in Singapore public law: Autochthonous evolution to buttress good governance and the Rule of Law - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2017)
Central to the separation of powers and the rule of law, judicial review empowers the courts to examine the exercise of discretionary power. While there is no general doctrine of deference, judical review in Singapore emphasises the green-light approach in facilitating good governance, and is sensitive to the political, socio-cultural and economic context. However, the jurisprudence also indicates a nuanced and robust approach to better regulate the decision-makers' latitude. A categorical approach towards justiciability is eschewed, and judicial scrutiny adopts varying intensities of review, taking into account the rights of the individual vis-a-vis the fair and just protection of governmental autonomy.